Design of a microelectromechanical systems microgripper with integrated electrothermal actuator and force sensor. (5th October 2016) - Yang, Sijie; Xu, Qingsong
This article presents the conceptual design of a novel compliant microelectromechanical systems (MEMS)-based gripper with integrated electrothermal actuator and electrothermal force sensor. By this design solution, the device possesses some unique characteristics including a small and compact footprint size, and a large driving force by the thermal actuator. Owing to the use of a compliant rotational bearing, a large gripping range is obtained. The sensing arm has a capability of detecting the force transmitted from the left arm so as to prevent the damage of the grasped object. Analytical models are developed to evaluate the statics and dynamics performance of the gripper. Simulation results show that the thermal actuator produces sufficient gripping force to execute the gripping operation with a range of 80 µm under a low input voltage of 6 V. Moreover, the results of the established theoretical models match well with the finite element analysis (FEA) simulation results, which verifies the feasibility of the proposed gripper design.